Towards a framework for delineating sub-districts for primary health care administration in rural Ghana: A case study using GIS - Kofie, R.Y.; Møller-Jensen, L. (Norsk Geografisk Tidsskrift, 2001)
This paper examines the need to carry out primary health care administration, programming and planning beyond the established 110 districts in Ghana. The framework for delimiting the sub-districts is offered by the availability of digital data such as the district boundary, site location, road network and population. Using the specified travel distance from predetermined sites, network analysis generates approximate polygons around the health centres to create functional areas - the health sub-districts. Additional sites are proposed based on a set of criteria which includes proximity, centrality, population and existing level of infrastructural development in an attempt to improve coverage and bring the total utilization of health facilities closer to 100% in the study area.
Keywords: Network analysis; Primary health care; Sub-districts